Nitric oxide production and antioxidant function during viral infection of the coccolithophore Emiliania huxleyi - Schieler, B.; Soni, M.; Brown, C.; Coolen, Marco; Fredricks, H.; Van Mooy, B.; Hirsh, D.; Bidle, K. (2019)
Emiliania huxleyi is a globally important marine phytoplankton that is routinely infected by viruses. Understanding the controls on the growth and demise of E. huxleyi blooms is essential for predicting the biogeochemical fate of their organic carbon and nutrients. In this study, we show that the production of nitric oxide (NO), a gaseous, membrane-permeable free radical, is a hallmark of early-stage lytic infection in E. huxleyi by Coccolithoviruses, both in culture and in natural populations in the North Atlantic. Enhanced NO production was detected both intra- and extra-cellularly in laboratory cultures, and treatment of cells with an NO scavenger significantly reduced viral production. Pre-treatment of exponentially growing E. huxleyi cultures with the NO donor S-nitroso-N-acetylpenicillamine (SNAP) prior to challenge with hydrogen peroxide (H2O2) led to greater cell survival, suggesting that NO may have a cellular antioxidant function. Indeed, cell lysates generated from cultures treated with SNAP and undergoing infection displayed enhanced ability to detoxify H2O2. Lastly, we show that fluorescent indicators of cellular ROS, NO, and death, in combination with classic DNA- and lipid-based biomarkers of infection, can function as real-time diagnostic tools to identify and contextualize viral infection in natural E. huxleyi blooms.